1993
DOI: 10.1042/bj2960361
|View full text |Cite
|
Sign up to set email alerts
|

Functional, spectroscopic and structural properties of haemoglobin from chamois (Rupicapra rupicapra) and steinbock (Capra hircus ibex)

Abstract: The functional and spectroscopic properties of chamois (Rupicapra rupicapra) and steinbock (Capra hircus ibex) haemoglobin (Hb) have been studied with special reference to the action of allosteric effectors and temperature. Moreover, the amino acid sequences of the N-terminal segments of the alpha- and beta-chains have been determined. The present results indicate that chamois and steinbock Hbs display a low affinity for O2, which appears to be modulated in vivo by Cl- ions rather than 2,3-bisphosphoglycerate.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
6
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
(86 reference statements)
3
6
0
Order By: Relevance
“…The amplitude of the Bohr effect (Δ log p 50 /ΔpH, where ΔpH = 6.5–8.0) for O 2 binding to red deer Hb is –0.47 under stripped conditions, and –0.51 and –0.57 in the presence of Cl − and/or of both Cl − and GriP 2 , respectively. These values are similar to those reported for chamois and steinbock Hb [11], but higher than those observed for other ruminant Hbs such as reindeer [19], sheep ( Ovis aries ), mouflon ( Ovis gmelini musimon ) [20] and ox ( Bos tauros ) [2].…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The amplitude of the Bohr effect (Δ log p 50 /ΔpH, where ΔpH = 6.5–8.0) for O 2 binding to red deer Hb is –0.47 under stripped conditions, and –0.51 and –0.57 in the presence of Cl − and/or of both Cl − and GriP 2 , respectively. These values are similar to those reported for chamois and steinbock Hb [11], but higher than those observed for other ruminant Hbs such as reindeer [19], sheep ( Ovis aries ), mouflon ( Ovis gmelini musimon ) [20] and ox ( Bos tauros ) [2].…”
Section: Resultssupporting
confidence: 86%
“…Two Hb phenotypes (lane 2 and 3) differing in the α‐chain are compared with the heterozygote (lane 1) containing both of them. Separation was by PAGE in the presence of acetic acid, 8 m urea and Triton X‐100 [10–12]. The gel was stained with 0.5% Coomassie blue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Bohr coefficient for oxygen binding (Δlog P 50 /ΔpH at the midpoint of the transition) to red deer Hb is −0.51 in the presence of physiological concentration of chloride. These values are similar to those reported for chamois and steinbock (Ascenzi et al. 1993), but higher than those observed for other ruminant Hbs such as reindeer (Giardina et al.…”
Section: Mammals and Cold Environmentssupporting
confidence: 89%
“…The Bohr coefficient for oxygen binding (Dlog P 50 /DpH at the midpoint of the transition) to red deer Hb is )0.51 in the presence of physiological concentration of chloride. These values are similar to those reported for chamois and steinbock (Ascenzi et al 1993), but higher than those observed for other ruminant Hbs such as reindeer ), sheep (Corda et al 1997), mouflon (Coletta et al 1992), and ox (Giardina et al 1990a). The increased Bohr effect for red deer Hb oxygenation compared with other ruminant Hbs may be of importance for living at high altitude.…”
Section: Mammals and Cold Environmentssupporting
confidence: 88%